2017
DOI: 10.25115/ejrep.v9i23.1427
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Reasoning Ability, Self-Efficacy, and Value Beliefs in a Reform Based University Statistics Course

Abstract: Introduction. The study investigated the degree to which students" statistical reasoning abili-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Central tendency Students have misconceptions about measures of central tendency: mode (Huck, 2009), median (Cooper & Shore, 2008), and mean (Olani, Hoekstra, Harskamp, & Van der Werf, 2010). When asked to identify the three measures of central tendency from a histogram, where frequency information is displayed on the y-axis, students make some common errors that stem from misinterpreting the information portrayed by the axes (reading the y-axis as data values and not frequency) and by the bars.…”
Section: Misconceptions About Summary Statisticsmentioning
confidence: 99%
“…Central tendency Students have misconceptions about measures of central tendency: mode (Huck, 2009), median (Cooper & Shore, 2008), and mean (Olani, Hoekstra, Harskamp, & Van der Werf, 2010). When asked to identify the three measures of central tendency from a histogram, where frequency information is displayed on the y-axis, students make some common errors that stem from misinterpreting the information portrayed by the axes (reading the y-axis as data values and not frequency) and by the bars.…”
Section: Misconceptions About Summary Statisticsmentioning
confidence: 99%
“…Nevertheless, high school students appear to have poor statistical reasoning ability [2], and they often harbor numerous misconceptions about statistical reasoning, as found in our preliminary and earlier studies. For instance, in descriptive statistics, students frequently make mistakes in answering questions regarding measures of central tendency [3,4] and variability [5–7]. Statistical reasoning is a neglected area, particularly compared to the areas of statistical literacy and statistical thinking [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such research, however, is considerably lacking in the Caribbean region. Given the many questions that remain on the potential impact of prior performance in mathematics on the statistical performance of university students (Macher et al, 2011;Olani et al, 2011), the general anxieties related to statistics (Macher et al, 2013), the need for comparative data on other populations of students within the field of statistics education, and the empirical abyss that exists within the Caribbean, the study asked the following questions:…”
Section: Caribbean Contextmentioning
confidence: 99%
“…Yet another group of scholars has explored mathematical anxiety, defined in many cases as the extent to which students are worried about working with and manipulating numbers or their problem-solving skills (Ashcraft & Krause, 2007;Onwuegbuzie, 1997;Paechter et al, 2017;Zeidner, 1991). This line of investigation on previous mathematics performance, has spurred related studies on the relationship between PMP, SA, and EFP (Olani et al, 2011;Paechter et al, 2017). Given the many questions around the effects of previous mathematics performance on statistical performance Paechter et al (2017) contended that PMP remains necessary, but not sufficient to explain reported variability in students' EFP in statistics courses.…”
Section: Previous Mathematics Performance (Pmp)mentioning
confidence: 99%